The Association between Omeprazole Dosing and Hypomagnesemia in Patients with Cardiovascular Disorders - Abuelsoud, Nermeen (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Patients with acute coronary syndrome should be treated with proton-pump inhibitors (PPIs) to decrease the gastrointestinal complications and hemorrhage associated with antiplatelets use. Hypomagnesemia associated with PPIs is not confirmed yet but if it is confirmed, it may explain the reason of cardiovascular risks associated with PPIs use. Aims: The aims of this study were to determine the association between omeprazole and hypomagnesemia, study the effect of different omeprazole doses in the occurrence of hypomagnesemia, and study the factors that may contribute to this hypomagnesemia. Methods: Over a 1-year period, all patients receiving omeprazole for more than 1 year admitted to the cardiac care unit were enrolled in this study. Patients were divided to three groups according to the omeprazole doses. The association between omeprazole dose and the presence of hypomagnesemia was assessed and compared between the three groups. Results: A total of 105 patients were enrolled in this study. The mean follow-up duration during hospitalization was 5.2 ± 2.9 days. All factors that may affect the incidence of hypomagnesemia were compared between the three groups and there was not any statistically significant difference between the three groups in relation to patient’s age, sex, presence of diabetes mellitus, and concurrent use of digoxin or diuretics. The incidence of hypomagnesemia between the 3 groups was not statistically significant but it was clinically significant. Conclusion: The hypomagnesemia associated with omeprazole may be dose related. This hypomagnesemia may explain the occurrence the cardiovascular events (arrhythmias and sudden death) after omeprazole use, but further studies are needed.